Apakah Ekspresi Cinta Memprediksi Perasaan Dicintai? Kajian Bahasa Cinta Pasif dan Aktif - Edwin Adrianta Surijah; Ni Kadek Prema Dewi Sabhariyanti; Supriyadi Supriyadi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
This research aims to discuss theories of Love especially in typology perspective which included current Five Love Languages (FLL) theory. This research also examined whether someone who feels loved based on a certain aspect of FLL would also express love in a similar fashion. FLL scale was divided into passive (felt love) and active (express love) form. 637 participants who were/are in a romantic relationship responded to both scales. Regression analysis examined the contribution from each of active FLL aspect toward passive FLL aspects. The result showed passive FLL was determined by active FLL expression and similar passive-active aspects showed the strongest relationship. The result brought implication to future study and on how to better understand a couple’s need to feel loved.